2003
DOI: 10.1161/01.cir.0000072793.81076.d4
|View full text |Cite
|
Sign up to set email alerts
|

Enalapril Decreases the Incidence of Atrial Fibrillation in Patients With Left Ventricular Dysfunction

Abstract: Background— Atrial fibrillation (AF) is frequently encountered in patients with heart failure (HF) and is also a predictor of morbidity and mortality in this population. Recent experimental studies have shown electrical and structural atrial remodeling with increased fibrosis in animals with HF and have suggested a preventive effect of ACE inhibitors (ACEi) on the development of AF. To verify the hypothesis that ACEi prevent the development of AF in patients with HF, we conducted a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 520 publications
(109 citation statements)
references
References 35 publications
5
97
0
7
Order By: Relevance
“…A similar finding was observed in patients with and without CHF at baseline. In comparison, post‐hoc analyzes of randomized, controlled trials in patients with CHF but without known AF have suggested that RAS inhibition might reduce the incidence of new‐onset AF 33, 34, 35. In contrast, 2 prospective, randomized trials on patients with AF did not show beneficial effects of RAS inhibition with regard to future AF burden similar to our findings 36, 37.…”
Section: Discussionsupporting
confidence: 83%
“…A similar finding was observed in patients with and without CHF at baseline. In comparison, post‐hoc analyzes of randomized, controlled trials in patients with CHF but without known AF have suggested that RAS inhibition might reduce the incidence of new‐onset AF 33, 34, 35. In contrast, 2 prospective, randomized trials on patients with AF did not show beneficial effects of RAS inhibition with regard to future AF burden similar to our findings 36, 37.…”
Section: Discussionsupporting
confidence: 83%
“…22 A clinical counterpart to this prevention aspect of therapy with angiotensin-converting enzyme inhibitors has been observed in clinical situations, in which it has been shown that these drugs seem to retard development of AF in certain patient subsets. 23,24 Nevertheless, once extensive structural remodeling (fibrosis) has occurred, substrate/structural remodeling becomes the dominant feature of the pathophysiology. Dominance of structural remodeling is manifest as inability to maintain sinus rhythm despite aggressive therapy.…”
Section: Inside the Clinician's Boxmentioning
confidence: 99%
“…Experimental and observational clinical data supported reninangiotensin-aldosterone blockers in AF prevention schemes 28,29 , but subsequent large randomized trials did not demonstrate a clinical benefit in patients without an established indication for these substances 30,31 . Drugs with anti-inflammatory and antioxidative properties that were tested for the prevention of AF in several settings showed mixed outcomes 23,[32][33][34][35] .…”
mentioning
confidence: 99%